Kajian Literatur: Analisis Fenomena Gunung Lumpur Beserta Karakteristik Lumpur di Bledug Kuwu Jawa Tengah - Safitri, Erinda Fazila; Nurita, Tutut; Amarna, Anindya Dhara; Mardianti, Audrey (Jurnal Sains Geografi, 2024)
The phenomenon of the Bledug Kuwu mud volcano in Kuwu Village, Grobogan Regency, Central Java, has attracted attention as a natural resource with significant economic, industrial, ecological, and medical potential. This research consolidates previous findings to provide a comprehensive understanding of the characteristics and utilization potential of Bledug Kuwu mud. The research method employed is a literature review study, with descriptive analysis of data collected through article searches and information synthesis. The results reveal the characteristics of the mud, including valuable mineral content such as lithium, kaolinite, and calcite, as well as the presence of halophilic bacteria with benefits in industry, environmental conservation, and medicine. In conclusion, Bledug Kuwu is not only a geological phenomenon but also a natural resource with significant economic, ecological, and medical value. This potential can be optimized through further research and sustainable technological development. Keyword: Bledug Kuwu, Mud volcano, Mud characteristic, Mud utilization